Development and Validation of a Highly Sensitive LC–MS/MS Method for the Precise Quantification of Sitagliptin in Human Plasma and Its Application to Pharmacokinetic Study - Yuna Song; Wang-Seob Shim; Eunseo Song; Yebeen Park; Bo-Hyung Kim; Sangmin Lee; Eun Kyoung Chung; Kyung-Tae Lee (Molecules)
Sitagliptin is an orally bioavailable selective DPP4 inhibitor that reduces blood glucose levels without significant increases in hypoglycemia. The aim of this study was to design and validate an innovative, rapid, and highly sensitive LC–MS/MS assay for the precise measurement of sitagliptin concentrations in human plasma. This analytical method, utilizing sitagliptin-d4 as the internal standard, is performed using only 100 μL of plasma and a liquid–liquid extraction procedure based on methyl tert-butyl ether (MTBE). Chromatographic separation is expertly achieved with a Kinetex® C18 column under isocratic elution, employing a perfect 1:1 blend of 5 mM ammonium acetate (with 0.04% formic acid) and acetonitrile, and maintaining an efficient flow rate of 0.2 mL/min. Detection occurs in positive ionization mode through multiple reaction monitoring, precisely targeting transitions of m/z 408.2 → 193.0 for sitagliptin and 412.2 → 239.1 for the IS. The total runtime of this assay is under 2 min. Comprehensive validation in line with MFDS and FDA criteria demonstrates outstanding linearity (5–1000 ng/mL, r2 > 0.998), alongside impressive levels of accuracy, precision, recovery and sample stability. Due to its minimal sample requirement and high-throughput capability, the validated approach is highly appropriate for pharmacokinetic and bioequivalence assessments involving sitagliptin.